The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/antiox10030385
|View full text |Cite
|
Sign up to set email alerts
|

Light and CO2 Modulate the Accumulation and Localization of Phenolic Compounds in Barley Leaves

Abstract: Barley (Hordeum vulgare) accumulates phenolic compounds (PhCs), which play a key role in plant defense against environmental stressors as antioxidants or UV screening compounds. The influence of light and atmospheric CO2 concentration ([CO2]) on the accumulation and localization of PhCs in barley leaves was examined for two varieties with different tolerances to oxidative stress. PhC localization was visualized in vivo using fluorescence microscopy. Close relationships were found between fluorescence-determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…Hexoses were negatively correlated with ABA in the RDA graph (Figure 5). Moreover, the genotypes Barke and Bojos were previously characterized in our recent work on the accumulation of phenolic compounds in barley [20]. We found that Barke, considered an oxidative stress sensitive genotype, accumulated more hydroxybenzoic acids, while Bojos, an oxidative stress resistant genotype, accumulated more hydroxycinnamic acids.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Hexoses were negatively correlated with ABA in the RDA graph (Figure 5). Moreover, the genotypes Barke and Bojos were previously characterized in our recent work on the accumulation of phenolic compounds in barley [20]. We found that Barke, considered an oxidative stress sensitive genotype, accumulated more hydroxybenzoic acids, while Bojos, an oxidative stress resistant genotype, accumulated more hydroxycinnamic acids.…”
Section: Discussionmentioning
confidence: 59%
“…HXK is also involved in the downregulation of photosynthesis under elevated [CO 2 ] when plants lack sufficient sinks for the products of photosynthesis [15]. This study looks at how experimentally manipulated [CO 2 ] and light conditions modulate both the stomatal density and stomatal conductance alongside physiological processes in two barley varieties differing in sensitivity to oxidative stress and phenolic compound profiles [20]-oxidative stress sensitive Barke and oxidative stress resistant Bojos. To measure stomatal density, we used a novel automated approach-a convolution neural network (CNN).…”
Section: Introductionmentioning
confidence: 99%
“…However, we presume that the observed increase in AOX is at least partially caused by the significantly higher proportion of B-hydroxylated flavonoids (such as LUT, HFG, HSG) in extracts ( Figure 5 H) (AOX shows a higher correlation and dependency on the content of homoorientin derivatives, Supplementary Figure S2 vs. Figure S3 ) and hypothetically also due to higher content of FQA. The dominant contribution of blue light to the AOX capacity of PheCs may also be related to their localization since high PAR selectively accumulates PheCs in mesophyll cells, where they contribute to AOX rather than to UV-A shielding [ 18 ]. Nevertheless, the possible presence of other LMWA with strong antioxidant activity in extracts cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…PheCs play a role in plant defense against a wide range of stressors [ 16 ]. This large group of secondary metabolites includes photoprotective compounds, such as flavonoids and anthocyanins (important subclasses of PheCs), which absorb strong UV and PAR when localized in the epidermis [ 17 ] and parenchyma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ferulic and sinapic acid derivatives, acylated flavone glycosides, and hordatines, were found as drought‐responsive in leaves from young barley seedlings (Piasecka et al, 2017). Phenylpropanoid accumulation upon increasing CO 2 concentrations has also been observed (Hunt et al, 2021). Induction of specific phenylpropanoid branches during cold acclimation has been reported for winter cereals (NDong et al, 2003) and other plant species (Petridis et al, 2016; Solecka & Kacperska, 2003).…”
Section: Introductionmentioning
confidence: 91%